DEIXIS USED IN THE MOVIE “TOY STORY: LAMP LIFE” BY DISNEY - RULIK SETIANI; SINTA NOVIA; SIGIT SUHARJONO (JETA (Journal of English Teaching and Applied Linguistic), 2024)
This research is a deixis analysis which is one of the sciences of semantics. This study aims to classify deixis, to find the dominant deixis in movie, and to discover is there any deixis that cannot found in the movie. This research use qualitative descriptive strategy as the method. Researchers used a movie from Disney entitled "Toy Story: Lamp Life" as a medium for researching deixis. There are 5 types of deixis; person deixis, time deixis, place deixis, discourse deixis, and social deixis. Through the analysis process, it was founded 4 deixis but 1 deixis or social deixis is not founded, researchers used qualitative research method. After researchers classify the data, researchers found the dominant deixis in the movie "Toy Story: Lamp Life" is person deixis, and the deixis did not find is social deixis. Based on the result of the analysis, it is concluded that the movie has so many deixis that the students can use it to be a media to learn deixis in semantic learning.